Paratubal serous borderline tumor in an 85 years old woman: A case report - Jordy Mehawej; Nicole El Helou; Lina Wang; Paulette Mhawech-Fauceglia (Elsevier, 2020)
Paratubal cysts are incidental, common and benign lesions with few cases of borderline tumor and adenocarcinoma been reported in the literature.Herein, we are discussing a case of an 85 years old woman who visited her Obstetrics and Gynecologist for a chief complaint of post-menopausal bleeding. Physical examination revealed a slightly enlarged uterus. The diagnosis of fibroids were made on ultrasound.A total hysterectomy with bilateral salpingo-oophorectomy was performed without complications. The gross examination of the specimen was most remarkable for multiple intramural fibroids and a right simple paratubal cyst meausirng 1 × 1 cm. Microscopical evaluation of the paratubal cyst showed a simple cyst lined by stratified cuboidal epithelium with mild cytologic atypia and no stromal invasion, findings consistent with serous borderline tumor rising in a paratubal cyst. Due to the small size of the tumor and its confinement to the cyst, a follow-up was advised.Serous borderline tumors arising in paratubal cyst are very rare with only eight cases reported in the literature. Their existence should be acknowledged to plan patient treatment and outcome.